Communicating health and science to the public: a role for scientists and academic researchers - Basseal, Jocelyne Marie; McLaws, Mary-Louise; Scott, Sophie; Salmon, Sharon (Western Pacific Surveillance and Response, 2023)
As seen through the COVID-19 pandemic, effective and impactful communications are the cornerstone to improved public health. Communications increase awareness about a health issue or solution and play a significant role in shifting social norms by influencing attitudes. However, scientists and academic researchers remain separate from the journalists and media that report to the wider community. We provide our perspective on the need to merge and weave the media and science worlds together for greater impact.